A dictionary of locutions from liturgical books by protopriest A. I. Nevostruev (много-множу) - Maria Davydenkova; Nadezhda Kaluzhnina; Olga Strievskaya; Natalia Mazurina; Maria Strievskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This publication continues the edition of the dictionary and contains entries beginning with the letter м. Special features of this edition of the Dictionary, a list of sources, a list of abbreviations as well as explanatory notes were set out in detail in the preceding issues of St. Tikhon’s University Review. All previously published parts of the Dictionary together with the accompanying materials are available at http://pstgu.ru/faculties/philological/science/slov_Nevostr/